2022
DOI: 10.3390/curroncol29120729
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a Digital Multimodal Cancer Prehabilitation

Abstract: Introduction: There is growing evidence that prehabilitation programmes effectively improve the physical and psychological conditions of cancer patients awaiting treatment. During the pandemic, people with cancer were classed as vulnerable. To reduce risk to this population Kent and Medway Prehabilitation service transformed into a TeleHealth format. The aim of this study is to assess the impact on health-related quality of life (HRQoL) and the costs of a digital multimodal prehabilitation programme. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…58 In other cancer populations, multimodal prehabilitation including exercise, nutrition, and psychological interventions have been demonstrated to improve function and reduce healthcare-associated costs. 111,112 Dedicated prehabilitation for the neck and shoulder has also been shown in other cancer populations to reduce postoperative pain and healing time and improve functional outcomes. 113 Future high-quality studies are needed on multimodal prehabilitation in HNC survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 In other cancer populations, multimodal prehabilitation including exercise, nutrition, and psychological interventions have been demonstrated to improve function and reduce healthcare-associated costs. 111,112 Dedicated prehabilitation for the neck and shoulder has also been shown in other cancer populations to reduce postoperative pain and healing time and improve functional outcomes. 113 Future high-quality studies are needed on multimodal prehabilitation in HNC survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our review only identified one study evaluating a multimodal prehabilitation program consisting of swallowing exercises and whole-body resistance training during radiotherapy 58 . In other cancer populations, multimodal prehabilitation including exercise, nutrition, and psychological interventions have been demonstrated to improve function and reduce healthcare-associated costs 111,112 . Dedicated prehabilitation for the neck and shoulder has also been shown in other cancer populations to reduce postoperative pain and healing time and improve functional outcomes 113 .…”
Section: Discussionmentioning
confidence: 99%
“…Between January 2022 and October 2023, ten studies have specifically addressed the cost balance of introducing prehabilitation programs before surgery [9 ▪ ,10–15,16 ▪ ,17,18 ▪▪ ]. Various types of programs were evaluated including physical, nutritional, and multimodal (including a combination of physical, nutritional, and psychological support).…”
Section: Clinical Evidence On Cost-effectiveness Of Prehabilitationmentioning
confidence: 99%
“…Seven original studies analysed the cost-effectiveness of multimodal prehabilitation programs in patients scheduled for elective major digestive, cardiac, thoracic, gynaecologic surgeries, heart transplant, TKA or cancer treatment [12–15,16 ▪ ,17,18 ▪▪ ]. The studies recorded similar endpoints that included nutritional, physical and psychological status, postoperative complications, LoH and length of ICU stay, hospitalization costs, and quality of life.…”
Section: Cost- Effectiveness Of Multimodal Prehabilitation Programsmentioning
confidence: 99%
See 1 more Smart Citation